2017
DOI: 10.5194/acp-17-12941-2017
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization and source identification of PM<sub>2.5</sub> at multiple sites in the Beijing–Tianjin–Hebei region, China

Abstract: Abstract. The simultaneous observation and analysis of atmospheric fine particles (PM 2.5 ) on a regional scale is an important approach to develop control strategies for haze pollution. In this study, samples of filtered PM 2.5 were collected simultaneously at three urban sites (Beijing, Tianjin, and Shijiazhuang) and at a regional background site (Xinglong) in the Beijing-Tianjin-Hebei (BTH) region from June 2014 to April 2015. The PM 2.5 at the four sites was mainly comprised of organic matter, secondary in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(104 citation statements)
references
References 99 publications
(84 reference statements)
6
95
3
Order By: Relevance
“…The source profile could be explained by about five to six factors, including secondary source, industry, traffic (vehicle), coal combustion, biomass burning, and dust, primarily consistent with this study. As for the autumn source contributions, the results in this study were generally acceptable, compared with the results from Huang et al [83] and published data from the local government [84]. The higher proportion of secondary source than the annual average level [85] may result from intensive biomass burning during the study period.…”
Section: Sectoral Source Apportionment and Regional Source Identificasupporting
confidence: 68%
See 1 more Smart Citation
“…The source profile could be explained by about five to six factors, including secondary source, industry, traffic (vehicle), coal combustion, biomass burning, and dust, primarily consistent with this study. As for the autumn source contributions, the results in this study were generally acceptable, compared with the results from Huang et al [83] and published data from the local government [84]. The higher proportion of secondary source than the annual average level [85] may result from intensive biomass burning during the study period.…”
Section: Sectoral Source Apportionment and Regional Source Identificasupporting
confidence: 68%
“…C6 mainly represented the mid-BTH region, involving several heavily polluted cities such as Tangshan (TS), Tianjin (TJ), Langfang (LF), and Baoding (BD). Previous studies showed the component of OC in this area was mostly emitted from fuel (e.g., coal and oil) burning [83]. Among the cities, TJ had a substantial vehicle population of 2.74 million in 2016 [89] and TS is famous for its steel production, powered by great quantities of coal burning [90].…”
Section: Chemical Distribution and Transport Pathwaysmentioning
confidence: 99%
“…5a), implying ambient PAHs underwent photochemical degradation and were influenced by vehicle emissions and coal combustion. It was reported that the free ends of C-C scission products of PAHs remain tethered together, which prevent fragmentation and help in forming more functional groups from the reactions with OH q radical (Hunter et al, 2014) -ultimately forming the lowvolatility species which can condense on the particle phase. There were several deviation points in the lower-left corner, and the values were smaller than the values of the tunnel and vehicle source profile, indicating mixed influence from traffic origins and degradation.…”
Section: Degradation Of Organicsmentioning
confidence: 99%
“…To develop strategies for controlling atmospheric pollution caused by particulate matter, receptor-based models (e.g., positive matrix factorization, PMF) have been widely applied to quantitatively apportion sources of particulate matter Li et al, 2016;Huang et al, 2017). However, the output factors of the receptor model are not necessarily emission sources, because there exist some atmospheric processes like photodegradation or gas-particle partitioning.…”
Section: Introductionmentioning
confidence: 99%
“…The second source factor was linked to traffic-related emissions, and it was characterized by strong loadings of EC (42.1 %) and Cu (40.7 %) and moderate contributions of OC (29.1 %), Zn (27.1 %), and Br (22.2 %). Previous studies have indicated that carbonaceous aerosols are components of gasoline and diesel engine exhaust (Cao et al, 2005), and therefore EC and OC have been used as indicators for motor vehicle emissions (Chalbot et al, 2013;Khan et al, 2016a), and Br may also be emitted from internal combustion engines (Bukowiecki et al, 2005). Aerosol Cu and Zn are derived from other types of vehicle emissions, including those associated with lubricant and oil, brake linings, metal brake wear, and tires (Lin et al, 2015).…”
Section: Estimates Of Source Contributionsmentioning
confidence: 99%